TAPS HEXAGONAL EN EL DESARROLLO DEL PENSAMIENTO LÓGICO - Rojas, Ivan (2019)
The game consists of arming the taps hex numbers and using mathematical signs of the core operations, intermediate and advanced levels as it is. The student must try to form 5 to more equations in a short time with taps hexagonal. In this project we chose the hexagonal that are better suited to our interests and cover the fields of mathematics as there are jobs that are not dedicated to the levels of transfer and the social dimensions.